Non-Newtonian fluid gating membranes with acoustically responsive and self-protective gas transport control. Issue 3 (21st December 2022) - Liu, Jing; Sheng, Zhizhi; Zhang, Mengchuang; Li, Jianyu; Zhang, Yunmao; Xu, Xue; Yu, Shijie; Cao, Min; Hou, Xu
Abstract : Non-Newtonian fluid gating membranes have been constructed for contactless regulation of gas release and spontaneous blockage of transient high-pressure gas. Abstract : Control of gas transport through porous media is desired in multifarious processes such as chemical reactions, interface absorption, and medical treatment. Liquid gating technology, based on dynamically adaptive interfaces, has been developed in recent years and has shown excellent control capability in gas manipulation—the reversible opening and closing of a liquid gate for gas transport as the applied pressure changes. Here, we report a new strategy to achieve self-protective gas transport control by regulating the dynamic porous interface in a non-Newtonian fluid gating membrane based on the shear thickening fluid. The gas transport process can be suspended and restored via modulation of the acoustic field, owing to the transition of particle-to-particle interactions in a confined geometry. Our experimental and theoretical results support the stability and tunability of the gas transport control. In addition, relying on the shear thickening behaviour of the gating fluid, the transient response can be achieved to resist high-impact pressure. This strategy could be utilized to design integrated smart materials used in complex and extreme environments such as hazardous and explosive gas transportation.